Control-Surface Structural Nonlinearities in Aeroelasticity: A State of the Art Review - Bueno, Douglas D. [UNESP]; Wayhs-Lopes, Larissa D. [UNESP]; Dowell, Earl H. (Amer Inst Aeronautics Astronautics, 2022)
This paper presents a review and assessment of more than six decades of research in aeroelastic stability, including control-surface nonlinearities. The work covers free play, friction, cubic stiffness, and an actuator in a failure mode. The basic modeling of each nonlinearity is introduced to provide insights for those new in this field. A detailed description of findings is included that shows the two and three degrees of freedom typical section model has been widely investigated. For this type of system, it is noted that usually a nonlinearity in the pitch degree of freedom generates more complex limit-cycle oscillations than a nonlinearity in the control-surface rotation. A brief introduction of the methods most commonly employed in the theoretical and computational analyses is presented, including their pros and cons, as reported in the literature. This paper explores challenges yet to be overcome and opportunities for further studies.